The Influence of Parents Parenting Patterns on the Learning Achievement of Class X Students : (at Madrasah Aliyah Negeri Putussibau) - Sarono Wijio (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
Parental parenting is a pattern of interaction between parents and children during the nurture and care period with the aim of guiding and educating their children in a better life in a family environment. The role of the family, especially parents, is very important in educating children in terms of religious, social, and individual reviews so that they are able to foster the development of children's personalities into adult humans who have positive attitudes towards religion, strong and independent personalities, physical and spiritual potential as well as optimal intellectual development. This study aims to determine how the parenting style is applied by parents to their children. After it is known how the parenting style is applied, the next step is to look for the influence of parenting styles on the learning achievement of class X students of state madrasah aliyah droppies. This research is a descriptive correlational study, using a quantitative approach. The data collection methods used were questionnaires, interviews and documentation methods. The subjects of this research were 118 class X students and a sample of 30 students or 25% of the total population was taken. Analysis of the data used in this study using descriptive statistics and simple regression. From the results of the descriptive analysis, it was obtained: (a) the parenting patterns used by the parents of the students were a mixture of three types of parenting, namely democratic, authoritarian, and permissive with the following details: 32% democratic, 35% authoritarian, and 47% permissive. (b) the learning achievement of the 60 students was mostly at a high level of achievement with a frequency of 32 students or 53%. From the results of the simple linear regression test, it is obtained: the r number is 0.638 which is greater than the significance level of 0.5, so the null hypothesis is rejected and the working hypothesis is accepted. The adjusted coefficient of determination (Adjusted R Square) is 0.400, which means that the dependent variable on learning achievement is explained by the independent variable of parenting by 40% while the remaining 60% is explained by other variables outside the variables used in this study.